Epithelial HIF2 alpha expression induces intestinal barrier dysfunction and exacerbation of arthritis - Wen, Jinming; Lyu, Pang; Stolzer, Iris; Xu, Jin; Gießl, Andreas; Lin, Zhen; Andreev, Darja; Kachler, Katerina; Song, Rui; Meng, Xianyi; Cao, Shan; Guggino, Giuliana; et al. (Annals of the Rheumatic Diseases, 2022)
To investigate how the mucosal barrier in the intestine influences the development of arthritis, considering that metabolic changes in the intestinal epithelium influence its barrier function. Intestinal HIF2α expression peaked at onset of experimental arthritis and RA. Conditionally, deletion of HIF2α in gut epithelial cells inhibited arthritis and was associated with improved intestinal barrier function and less intestinal and lymphatic Th1 and Th17 activation. Mechanistically, HIF2α induced the transcription of the pore-forming claudin (CLDN)-15, which inhibits intestinal barrier integrity. Furthermore, treatment with HIF2α inhibitor decreased claudin-15 expression in epithelial cells and inhibited arthritis and littermate control mice. The gut intestinal HIF2α target genes were delineated by chromatin immunoprecipitation and luciferase experiments. Furthermore, pharmacological HIF2α inhibitor PT2977 was used for inhibition of arthritis. These findings show that the HIF2α-CLDN15 axis is critical for the breakdown of intestinal barrier function at onset of arthritis, highlighting the functional link between intestinal homeostasis and arthritis.
CRIS-Team WoS Importer:2022-07-01
Keywords: Arthritis; Arthritis; Experimental; Inflammation.

Estrogen-mediated downregulation of HIF-1 alpha signaling in B lymphocytes influences postmenopausal bone loss - Meng, Xianyi; Lin, Zhen; Cao, Shan; Janowska, Iga; Sonomoto, Koshiro; Andreev, Darja; Knab, Katharina; Wen, Jinming; Knaup, Karl; Krönke, Gerhard; Rizzi, Marta; Schett, Georg; et al. (Bone Research, 2022)
In the bone marrow, B cells and bone-resorbing osteoclasts colocalize and form a specific microenvironment. How B cells functionally influence osteoclasts and bone architecture is poorly understood. Using genetically modified mice and high-throughput analyses, we demonstrate that prolonged HIF-1 alpha signaling in B cells leads to enhanced RANKL production and osteoclast formation. In addition, deletion of HIF-1 alpha in B cells prevents estrogen deficiency-induced bone loss in mice. Mechanistically, estrogen controls HIF-1 alpha protein stabilization through HSP70-mediated degradation in bone marrow B cells. The stabilization of HIF-1 alpha protein in HSP70-deficient bone marrow B cells promotes RANKL production and osteoclastogenesis. Induction of HSP70 expression by geranylgeranylacetone (GGA) administration alleviates ovariectomy-induced osteoporosis. Moreover, RANKL gene expression has a positive correlation with HIF1A expression in human B cells. In conclusion, HIF-1 alpha signaling in B cells is crucial for the control of osteoclastogenesis, and the HSP70/HIF-1 alpha axis may serve as a new therapeutic target for osteoporosis.
CRIS-Team WoS Importer:2022-03-04

Expression of HIF1α in intestinal epithelium restricts arthritis inflammation by inhibiting RIPK3-induced cell death machinery - Lyu, Pang; Wen, Jinming; Zhang, Wenshuo; Liu, Ning; Stolzer, Iris; Gießl, Andreas; Jia, Yewei; Mauro, Daniele; Zhang, Fulin; Ciccia, Francesco; Soulat, Didier; Günther, Claudia; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives: To investigate the mechanism by which intestinal epithelial cell (IEC) death induces arthritis. Methods: IEC death was assessed by staining for necroptosis and apoptosis markers and fluorescence in situ hybridisation at different time points during collagen-induced arthritis (CIA). During the development of CIA, messenger RNA (mRNA) sequencing was performed, followed by Gene Ontology enrichment analysis of differentially expressed genes. Mice deficient for hypoxia-inducible factor 1α (Hif1a) in IECs (Hif1aΔIEC) were generated and induced for arthritis. mRNA sequencing, chromatin immunoprecipitated (ChIP) DNA sequencing and ChIP-qualitative PCR were performed on IECs from Hif1aΔIEC mice and littermate controls. Effects of HIF1α stabilisation by inhibition of prolyl hydroxylase domain-containing enzymes and treatment with the inhibitor of receptor-interacting protein kinase-3 (RIPK3) were tested in intestinal organoids and in CIA. Results: IEC underwent apoptotic and necroptotic cell death at the onset of arthritis, leading to impaired gut barrier function. HIF1α was identified as one of the most upregulated genes in IECs during the onset of arthritis. Deletion of Hif1a in IEC enhanced IEC necroptosis, triggered intestinal inflammation and exacerbated arthritis. HIF1α was found to be a key transcriptional repressor for the necroptosis-inducing factor RIPK3. Enhanced RIPK3 expression, indicating necroptosis, was also found in the intestinal epithelium of patients with new-onset rheumatoid arthritis. Therapeutic stabilisation of HIF1α as well as small-molecule-based RIPK3 inhibition rescued intestinal necroptosis in vitro and in vivo and suppressed the development of arthritis. Conclusion: Our results identify IEC necroptosis as a critical link between the gut and the development of arthritis.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Arthritis; Experimental; Arthritis; Rheumatoid; Immune System Diseases; Inflammation

INTESTINAL HIF1 alpha EXPRESSION PROTECTS AGAINST EPITHELIAL CELL DEATH IN ARTHRITIS - Lyu, Pang; Wen, Jinming; Stolzer, Iris; Gießl, Andreas; Song, Rui; Meng, Xiangjun; Cao, Shan; Günther, Claudia; Schett, Georg; Bozec, Aline (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Intratumor Heterogeneity Correlates With Reduced Immune Activity and Worse Survival in Melanoma Patients - Lin, Zhen; Meng, Xianyi; Wen, Jinming; Corral, José María; Andreev, Darja; Kachler, Katerina; Schett, Georg; Chen, Xiaoxiang; Bozec, Aline (Frontiers in Oncology, 2020)
Background: Human malignant melanoma is a highly aggressive, heterogeneous and drug-resistant cancer. Due to a high number of clones, harboring various mutations that affect key pathways, there is an exceptional level of phenotypic variation and intratumor heterogeneity (ITH) in melanoma. This poses a significant challenge to personalized cancer medicine. Hitherto, it remains unclear to what extent the heterogeneity of melanoma affects the immune microenvironment. Herein, we explore the interaction between the tumor heterogeneity and the host immune response in a melanoma cohort utilizing The Cancer Genome Atlas (TCGA). Methods: Clonal Heterogeneity Analysis Tool (CHAT) was used to estimate intratumor heterogeneity, and immune cell composition was estimated using CIBERSORT. The Overall Survival (OS) among groups was analyzed using Kaplan–Meier curves with the log-rank test and multivariate cox regression. RNA-seq data were evaluated to identify differentially expressed immunomodulatory genes. The reverse phase protein array (RPPA) data platform was used to validate immune responses at protein level. Results: Tumors with high heterogeneity were associated with decreased overall survival (p = 0.027). High CHAT tumors were correlated with less infiltration by anti-tumor CD8 T cells (p = 0.0049), T follicular cells (p = 0.00091), and M1 macrophages (p = 0.0028), whereas tumor-promoting M2 macrophages were increased (p = 0.02). High CHAT tumors correlated with a reduced expression of immunomodulatory genes, particularly Programmed Cell Death 1 (PD1) and its ligand PD-L1. In addition, high CHAT tumors exhibited lower immune Cytotoxic T lymphocytes (CTLs)-mediated toxicity pathway score (p = 2.9E−07) and cytotoxic pathway score (p = 2.9E−08). High CHAT tumors were also associated with a lower protein level of immune-regulatory kinases, such as lymphocyte-specific protein tyrosine kinase (LCK) (p = 3.4e−5) and spleen tyrosine kinase (SYK) (p = 0.0011). Conclusions: Highly heterogeneous melanoma tumors are associated with reduced immune cell infiltration and immune response activation as well as decreased survival. Our results reveal that intratumor heterogeneity is an indicative factor for patient survival due to its impact on anti-tumor immune response.
CRIS-Team Scopus Importer:2020-12-25
Keywords: immunomodulator; intratumor heterogeneity; melanoma; The Cancer Genome Atlas; tumor infiltrating lymphocytes

L-Arginine metabolism inhibits arthritis and inflammatory bone loss - Cao, Shan; Li, Yixuan; Song, Rui; Meng, Xianyi; Fuchs, Maximilian; Liang, Chunguang; Kachler, Katerina; Meng, Xinyu; Wen, Jinming; Schlötzer-Schrehardt, Ursula; Taudte, Verena; Geßner, Arne; et al. (Annals of the Rheumatic Diseases, 2023)
Objectives: To investigate the effect of the L-Arginine metabolism on arthritis and inflammation-mediated bone loss. Methods: L-Arginine was applied to three arthritis models (collagen-induced arthritis, serum-induced arthritis and human TNF transgenic mice). Inflammation was assessed clinically and histologically, while bone changes were quantified by μCT and histomorphometry. In vitro, effects of L-Arginine on osteoclast differentiation were analysed by RNA-seq and mass spectrometry (MS). Seahorse, Single Cell ENergetIc metabolism by profilIng Translation inHibition and transmission electron microscopy were used for detecting metabolic changes in osteoclasts. Moreover, arginine-Associated metabolites were measured in the serum of rheumatoid arthritis (RA) and pre-RA patients. Results: L-Arginine inhibited arthritis and bone loss in all three models and directly blocked TNFα-induced murine and human osteoclastogenesis. RNA-seq and MS analyses indicated that L-Arginine switched glycolysis to oxidative phosphorylation in inflammatory osteoclasts leading to increased ATP production, purine metabolism and elevated inosine and hypoxanthine levels. Adenosine deaminase inhibitors blocking inosine and hypoxanthine production abolished the inhibition of L-Arginine on osteoclastogenesis in vitro and in vivo. Altered arginine levels were also found in RA and pre-RA patients. Conclusion: Our study demonstrated that L-Arginine ameliorates arthritis and bone erosion through metabolic reprogramming and perturbation of purine metabolism in osteoclasts.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Arthritis; Inflammation; Osteoporosis